2020
DOI: 10.1002/ase.1965
|View full text |Cite
|
Sign up to set email alerts
|

Online Assessment of Applied Anatomy Knowledge: The Effect of Images on Medical Students' Performance

Abstract: Anatomical examinations have been designed to assess topographical and/or applied knowledge of anatomy with or without the inclusion of visual resources such as cadaveric specimens or images, radiological images, and/or clinical photographs. Multimedia learning theories have advanced the understanding of how words and images are processed during learning. However, the evidence of the impact of including anatomical and radiological images within written assessments is sparse. This study investigates the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…However, there were no significant differences in grades on the online laboratory quizzes administered before and after the Covid-19 shutdown (Table 3), and the final examination grades (remote) were markedly higher than the midterm examination grades (in-person) (Table 3). This was not overly surprising, given that previous research has shown that assessment modality does not significantly influence student achievement in anatomy (Attardi & Rogers, 2015), and it is, therefore, unclear if the use of two-dimensional cadaveric images in the learning activities and assessments put students at an actual performance disadvantage (Inuwa et al, 2012;Sagoo et al, 2021). However, it is equally unclear if all of the desired learning outcomes were attained, as the ability to identify anatomical structures on two-dimensional images may not offer reliable evidence of spatial understanding (Gonzales et al, 2020) or other nontraditional discipline-independent skills (Evans & Pawlina, 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…However, there were no significant differences in grades on the online laboratory quizzes administered before and after the Covid-19 shutdown (Table 3), and the final examination grades (remote) were markedly higher than the midterm examination grades (in-person) (Table 3). This was not overly surprising, given that previous research has shown that assessment modality does not significantly influence student achievement in anatomy (Attardi & Rogers, 2015), and it is, therefore, unclear if the use of two-dimensional cadaveric images in the learning activities and assessments put students at an actual performance disadvantage (Inuwa et al, 2012;Sagoo et al, 2021). However, it is equally unclear if all of the desired learning outcomes were attained, as the ability to identify anatomical structures on two-dimensional images may not offer reliable evidence of spatial understanding (Gonzales et al, 2020) or other nontraditional discipline-independent skills (Evans & Pawlina, 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…Successful outcomes of teaching in terms of establishing a deep understanding of the topic, which will benefit therapists in future practice often depend on the study methods adopted by students when learning anatomy (Criado‐Álvarez et al, 2017). While much of the literature comes from studies on medical program (Abdel Meguid & Khalil, 2017; Ang et al, 2018; Bohl & Gest, 2011; Sagoo et al, 2021; Santos et al, 2021; Smith et al, 2014; Smythe & Hughes, 2008; Wormald et al, 2009), relatively little is known about the favored pedagogical approaches for anatomy used in speech and language therapy program. Notwithstanding, while various pedagogies can be employed during teaching (Schofield, 2018; Skinder‐Meredith, 2010), student motivation is essential to successfully acquire knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Merzougui and colleagues investigate the impact of different question types and format on student perception versus student performance (Merzougui et al, 2021), while the effect of contextual information and images on student performance and the way in which students perceive clinically oriented questions, in particular, is also described (Sagoo et al, 2021). Adaptation of the traditional identification-based "spot-test" assessment to include a multiple-choice format is introduced and shown to be a suitably reliable and challenging alternative to a free-response question approach (Douglas-Morris et al, 2021).…”
Section: Assessing the Wider Outcomes Of Anatomy Educationmentioning
confidence: 99%